Development and psychometric testing of a scale for assessing the psychological birth trauma - Zhang, Ke; Wu, Meiliyang; Zeng, Tieying; Yuan, Mengmei; Chen, Ye; Yang, Lingyan (Frontiers in Psychology, 2023)
Background: Psychological birth trauma is widespread in postpartum women, and its harms are serious to mothers' health. Existing tools rely on posttraumatic stress disorder to evaluate, which cannot effectively evaluate its connotation. The aim of this study was to develop a new instrument for use to comprehensively assess the psychological birth trauma level of women after birth and test the scale's psychometric properties. Methods: The scale was developed and evaluated through item generation, expert consultation, pre-survey, and psychometric evaluation. A literature review, focus group, and individual deep semi-structured interviews were utilized to identify the scale items. The expert consultation evaluated the content validity. Psychometric testing was conducted in a convenience sample of 712 mothers within the first 72 hours postpartum who were recruited from three hospitals in China. Results: The total Cronbach alpha coefficient of the scale was 0.874. Exploratory factor analysis supported that the final scale consisted of four dimensions and fifteen items. The explanatory variance of the four factors was 66.724%. The four dimensions are named "being neglected", "out of control", "physiological emotional response", and "cognitive behavioral response". The results of the confirmatory factor analysis showed that the fit indices were all at acceptable and good levels. Conclusions: The 15-item Birth Trauma Scale is a valid and reliable tool to evaluate the psychological trauma of mothers who experienced spontaneous childbirth. The scale is a maternal self-assessment scale that can help women understand their mental health. Healthcare providers can identify key populations and intervene with them.